Latin American politics in the neoliberal era : the changing dynamics of class struggle - Veltmeyer, Henry (Emerald studies in state, politics and society, 2024)
Latin America has been a major focal point for analysis of the global class war over land and labor. Taking the region as a useful window for understanding the conditions generated by the global advance and dynamics of free market and corporate capitalism at play all over the world, Henry Veltmeyer scrutinizes the shifting dynamics of class struggle in Latin America against the background of neoliberalism. With a central focus on the left and right swings of the electoral politics pendulum, this is an up-to-date, detailed study of the historic rise and ravages of capitalism and the forces of both development and resistance that it generates in its mission to accumulate capital under any social and environmental cost. Based on decades of research and experience and several recent sojourns to diverse sites of class struggle in Argentina, Bolivia, Brazil, Ecuador and Mexico, Veltmeyer provides the knowledge needed to challenge the machinations of both the international capitalist class and the ruling class closer to home. Challenging centuries-old systems and barriers as the only study on the contemporary dynamics of the class struggle within the context of this region, this text fights back against the homogenous tides of class and capitalism to envision a richly diverse continent with more to offer than ever. It is compelling reading for scholars and students specializing in the politics and sociology of development, international political economy, political ecology, and Latin American studies.